Effect of clinical pathway regarding promoting quality nursing care of patients with myocardial infarction exposed to invasive procedures - ELsayed Shrief, Sheren; Abdelnaby Hamed, Laila (International Journal of Advanced Nursing Studies, 2018)
Myocardial infarction is theÂ deathÂ of myocardial tissueÂ because ofÂ extendedÂ lack ofÂ blood and oxygen. Clinical pathway has emerged as one of the mostÂ famous new initiatives alleged to lower costs whilst maintaining or even improving the satisfactoryÂ level ofÂ patientÂ care.Aim: to assess the effect of clinical pathway regarding promoting quality Nursing care of patients with MI exposed to invasive procedures through designing, Implementing, and evaluating the effect of clinical pathway intervention.Design: A quasi-experimental research design (pre posttest) changed intoÂ applied in this study.Setting: The study has been carried out in Beni-suef university Hospital, Zagazig University Hospitals.Sample: thirty nurses from the previously mentioned setting and thirty patients with myocardial infarction who are hospitalized and exposed to invasive procedures.Tools: Assessment questionnaire (pre/post test) sheet, An Observational Checklist, and Hamilton Anxiety Rating Scale (HAM-A).Results: more than fifty percent of a studied sample of nurses their ages ranged from 20-30yrs, the mean age was (29.1Â±3.4), females (66.9%), and have beenÂ trainedÂ in nursing college, their work experience ranged from half to one decade. There has been a statistically significant distinction concerning knowledge and practical abilities of studied nurses among pre and post application of clinical pathway. Recommendations: Extra new studies should be done for better assessment of the nurse's abilities and distribute educational booklets, pamphlets, and posters to all nurses with a purpose toÂ enhanceÂ theirÂ degreeÂ ofÂ knowledgeÂ andÂ skills.Â Â Â Keywords: Clinical Pathway, Quality Nursing Care, patients, and Myocardial Infarction.